Acute Mechanical Performance of Magmaris vs. DESolve Bioresorbable Scaffolds in a Real-World Scenario - Boeder, Niklas F.; Dörr, Oliver; Koepp, Tim; Blachutzik, Florian; Achenbach, Stephan; Elsässer, Albrecht; Hamm, Christian W.; Nef, Holger M. (Frontiers in Cardiovascular Medicine, 2021)
Background: After the bioresorbable PLLA-based vascular scaffold (Absorb BVS) was taken from the market due to its high adverse event rates, a magnesium-based scaffold (Magmaris) was introduced. Objective: To compare the acute performance of the sirolimus-eluting magnesium alloy Magmaris scaffold with that of the novolimus-eluting PLLA-based DESolve scaffold in terms of appropriate scaffold deployment using optical coherence tomography (OCT). Methods and Results: Data from the final OCT pullback of 98 patients were included (19 Magmaris, 79 DESolve) and analyzed at 1-mm intervals. The following indices were calculated: mean and minimal area, residual area stenosis, incomplete strut apposition, tissue prolapse, eccentricity index, symmetry index, strut fracture, and edge dissection. OCT showed a minimum lumen area for Magmaris vs. DESolve of 6.6 ± 1.6 vs. 6.0 ± 1.9 (p = 0.06). Scaffolds with residual area stenosis >20% were predominantly seen in the DESolve group (15.8 vs. 46.8%; p = 0.01). The mean eccentricity index did differ significantly (0.74 ± 0.06 vs. 0.63 ± 0.09; p < 0.001). No fractures were observed for Magmaris scaffolds, but 15.2% were documented for DESolve BRS (p < 0.001). Incomplete scaffold apposition area was significantly higher in the DESolve group (0.01 ± 0.02 vs. 1.05 ± 2.32 mm2; p < 0.001). Conclusion: This is the first study to compare the acute mechanical performance between Magmaris and DESolve in a real-world setting. The acute mechanical performance of Magmaris BRS seems to be superior to that of DESolve BRS, whereas OCT showed a good acute mechanical performance for both BRS in terms of generally accepted imaging criteria.